Surgical clinical trials for HPV-positive oropharyngeal carcinoma - Lin, Chen; Sharbel, Daniel D.; Topf, Michael C. (Frontiers in Oncology, 2022)
The treatment of HPV-positive oropharyngeal squamous cell carcinoma (OPSCC) continues to evolve as multiple ongoing and recently completed clinical trials investigate the role of surgery, radiation therapy, chemotherapy, and immunotherapy. Current trials are investigating transoral robotic surgery (TORS) in treatment de-escalation protocols in an effort to optimize quality of life, while maintaining historical survival rates. The advantage of TORS is its minimally invasive approach to primary resection of the tumor as well as valuable pathologic staging. The ORATOR trial reported poorer quality of life in patients treated with TORS compared to primary radiotherapy though this was not a clinically meaningful difference. The recently published ECOG 3311 trial showed that surgery can be used to safely de-escalate the adjuvant radiation dose to 50 Gy in intermediate-risk patients. In this review, we summarize and discuss the past and current clinical trials involving surgery in the treatment of HPV-positive OPSCC.